Cutaneous and Gastrointestinal Helminth Parasites of the fish Synodontis schall and Synodontis nigrita (Siluriformes: Mochokidae) from the Lower Ouémé Valley in South Benin. - DOUGNON, TOSSOU JACQUES; LALEYE, PHILIPPE A. (My University, 2012)
Since, approximately 2 decades, there has been a regression of fish captures in Benin and particularly in the Basin of Ouémé river. A high parasitic infestation which would affect negatively the dynamics of the halieutic population, would be one of the probable causes of this regression. The present study aims to inventory helminth parasites in Synodontis schall and Synodontis nigrita from the lower Ouémé valley in South Benin and to estimate their prevalence. A sample of 75 specimens of the 2 fish species was examined at the laboratory between September and October, 2011. The results revealed high parasitic prevalence in the two species: 82.14 and 78.72%, respectively. Six helminth genus were identified of which one digenean trematode (Clinostomum sp.), three nematodes (Cithariniella petterae, Procamallanus laeviconchus, Synodontisia thelastomoides) and two cestodes Stoeksia pujehuni and Lytocestus sp. Of the three parasites groups, nematodes are most abundant in both Mochokidae examined; they are 66.53 and 90.58% of parasites counted, respectively in S. schall and S. nigrita. Synodontisia thelastomoides has the highest prevalence: 46.43% in Synodontis schall and 42.55% in Synodontis nigrita.
Keywords: Prevalence; helminth; parasite; Synodontis schall; Synodontis nigrita; lower Ouémé valley; Benin